Effect of Cardiac Rehabilitation on Blood Pressure and Functional Capacity in Patients after Myocardial Infarction - Parvand, Mandana; Goosheh, Babak; Sarmadi, Alireza (Novelty in Biomedicine, 2016)
Background: Before the year 1950 treatment of myocardial Infarction patients was complete bed rest for several weeks and reduces physical activity for several months. Cardiac rehabilitation based on exercise training reduces the effects of deconditioning of bed rest. The primary purpose of this study was to determine the methods and means of prevention and treatment of coronary artery disease. Materials and Methods: This study was designed clinical trial and cross sectional study before and after intervention, the effect of our new protocol was assessed according to method of Bruce stress test. Measurement consisted of Blood Pressure and Functional Capacity, which were recorded and compared before and after intervention. Results: There was a significant increase in functional capacity according to method of Bruce stress test after ten session of training. The criterion deviation at functional capacity variable was 13.19±2.242 METS and 24.42±6.00 METS before and after 10 sessions. Respectively, this obtained METS (body oxygen survey at rest state equal to 3/5 milliliter oxygen to each kg person weight at minute) rise amount from secondary posttest to primary test (P<0.05). There was also a significant decrease in systolic blood pressure after ten session of training. The criterion deviation and average was 121.5±8.83 and 112.00±9.18 for systolic blood pressure. This decline amounts has a meaningful variable amount given P value <0.05. Conclusion: Cardiac rehabilitation can increase the performance of blood circulation and uptake of oxygen in body. These changes showed a significant increase in functional capacity it can also reduce resistance of blood circulation and showed a significant decrease in systolic blood pressure.